Massively parallel interrogation of human functional variants modulating cancer immunosurveillance - Ying Liu; Yongshuo Liu; Xuran Niu; Ang Chen; Yizhou Li; Ying Yu; Binrui Mo; Zhiheng Liu; Tao Xu; Jie Cheng; Zeguang Wu; Wensheng Wei (Signal Transduction and Targeted Therapy)
Abstract Anti-PD-1/PD-L1 immune checkpoint blockade (ICB) therapy has revolutionized clinical cancer treatment, while abnormal PD-L1 or HLA-I expression in patients can significantly impact the therapeutic efficacy. Somatic mutations in cancer cells that modulate these critical regulators are closely associated with tumor progression and ICB response. However, a systematic interpretation of cancer immune-related mutations is still lacking. Here, we harnessed the ABEmax system to establish a large-scale sgRNA library encompassing approximately 820,000 sgRNAs that target all feasible serine/threonine/tyrosine residues across the human genome, which systematically unveiled thousands of novel mutations that decrease or augment PD-L1 or HLA-I expression. Beyond residues associated with phosphorylation events, our screens also identified functional mutations that affect mRNA or protein stability, DNA binding capacity, protein-protein interactions, and enzymatic catalytic activity, leading to either gene inactivation or activation. Notably, we uncovered certain mutations that concurrently modulate PD-L1 and HLA-I expression, represented by the clinically relevant mutation SETD2_Y1666. We demonstrated that this mutation induces consistent phenotypic effects across multiple cancer cell lines and enhances the efficacy of immunotherapy in different tumor models. Our findings provide an unprecedented resource of functional residues that regulate cancer immunosurveillance, offering valuable guidance for clinical diagnosis, ICB therapy, and the development of innovative drugs for cancer treatment.